Interaction between co-deposited metals during stripping voltammetry at boron-doped diamond electrodes. - Foord, J; Eaton, K; Hao, W; Crossley, A (2005)
Electrochemical processes, which underlie the use of conductive diamond electrodes for the simultaneous detection of two or more metal ions in solution by anodic stripping voltammetry (ASV), have been investigated. The model analyte system studied contains the two metal species, Ag+(aq) and Pb2+(aq), and the experimental techniques employed include cyclic and square wave voltammetries, along with X-ray photoelectron spectroscopy and secondary electron microscopy. Although the bulk metallic forms of Ag and Pb are immiscible, several interactions in the system between the two metal species present are observed, which significantly influence the electrodeposition and electrodissolution processes which underlie ASV. The subsequent nucleation and growth of a given metal on the electrode surface is enhanced by the presence of the second metal on the surface. The encapsulation of one metal by the other, within the metal particulates that form on the electrode surface, significantly reduces the stripping yield at the potentials characteristic of the individual metals. The stripping potentials are also influenced by bonding interactions between deposited Ag and Pb, which broaden the characteristic stripping peaks in cyclic voltammetry, as well as producing underpotential deposition and stripping. Given these interactions, the extent to which ASV at diamond electrodes can be used to determine the solution concentrations of Ag+(aq) and Pb2+(aq) is considered.